Implementasi Media Interaktif Tableau Untuk Pengembangan Visualisasi Data ASN Menggunakan Metode ETL - Nikhlatul Maolah; Bambang Siswoyo (Ikatan Ahli Informatika Indonesia, 2024)
The State Civil Apparatus is a profession for Civil Servants (PNS) and government employees with work agreements who serve government agencies who are appointed by civil service development officials and entrusted with other state duties and are paid based on statutory regulations and provide professional and quality public services. However, the large amount of data from the number of State Civil Apparatus in the Cirebon district government office makes it difficult for decision-makers to understand and analyze the data. This study aims to develop data visualization for State Civil Apparatus (ASN) in sub-district offices through the application of interactive media Tableau using the ETL (Extract, Transform, Load) method. The extract stage is the data collection stage from the Cirebon district communications and information services office in the form of State Civil Apparatus (ASN) data, spatial group, education, age and religion. Transform is the process of changing data from a previous format to the desired format. At this stage, the data relationship process is carried out to adjust several types of variables. Load is the final process that functions to enter the data into the final target, namely into the Source data in Tableau. The aim of this research is to design ASN data visualization using the interactive media Tableau. Data visualization displays some visual data in the form of bar graphs. With the availability of information in data visualization, it can make it easier for stakeholders to make decisions. In this era of digitalization, the need for efficient and transparent data processing has become very important, especially in government agencies. Utilizing Tableau as an interactive data visualization tool and exploring a more informative dashboard presentation